Micro Business Assistance Model in Bogor Regency and Banjar City West Java Province - Epi Supiadi; Wawan Heryana; Popon Sutarsih (International Seminar on Social Work Update, 2023)
The large number of micro-entrepreneurs amid high poverty rates has encouraged research with the aim of finding and developing models of micro-enterprise assistance in Bogor Regency and Banjar City, with problematic subs: (1) Problems and potential for micro-enterprises; (2) The initial model for micro business assistance; and (3) The final model of micro business assistance. The method used is research and development with a quantitative and qualitative approach to descriptive statistical analysis, using the Accidental Sampling Technique to produce a main sample of 91 respondents and a supporting sample of 12 informants. Micro business problems include: capital with an index of 0.73; marketing with an index of 0.58; raw materials with an index of 0.64; technology with an index of 0.62; Management with an index of 0.68; Bureaucracy with an index of 0.50; infrastructure with an index of 0.55; partners/business networks with an index of 0.71. Potential to reach index 0.88. The initial model of mentoring includes planning; general data identification; excavation and deepening of problems; and follow up. The conclusions of the study: (1) the number of problems and the potential for micro-enterprises and assistance is higher in Bogor Regency than in Banjar City; (2) the development model for micro business assistance includes: preparation of a work plan; build relationships; identification and analysis of problems and assistance needs; draw up a solution plan; implementation of solutions; monitoring and evaluation; termination; further guidance. Keywords: Mentoring Model, Micro Enterprises, Problems and Potential.